Availability of in-situ reinforced active-transient liquid phase bond with good wettability for 70 vol.% SiCp/A356 composite using Al-Mg-Ga-Ti interlayer. (15th November 2016) - Zhang, Guifeng; Cai, Jie; Chen, Biqiang; Xu, Tingting
Abstract: For transient liquid phase bonding of as-cast 70 vol.% SiCp/A356 composite, Al-24Mg-16Ga-1Ti (wt.%) active braze was designed by adding Ti as melting point increaser (MPI) for Al into Al-Mg-Ga active alloy near eutectic composition to produce in-situ reinforcement by precipitating a fine and dispersive Ti-containing intermetallic compound as reinforcement within the solid-solution bond seam after isothermal solidification. Bonding was performed at three temperature levels of quasi-melting (450 °C), just fully melting (500 °C), and over melting (550 °C) for the braze under 0.5–1.75 MPa in argon. The braze was able to produce fine (less than 1 μm) and dispersive Ti-containing precipitated phase (Al-2Mg-1Ga-0.5Ti, at.%) as in-situ reinforcement only at 500 °C under medium pressure (1–1.5 MPa), increasing bond seam microhardness by 30 Hv over the matrix. The braze robustly showed good wettability for each temperature due to the matrix dissolution and detectable amorphous reaction products containing Mg and Ga on SiC surface. Higher temperature caused coarsening of needle-like Si-containing Al-Si-Ti precipitated phase while higher pressure produced blocky Al3 Ti with a shell of Mg and Ga. Sound joint produced at 500 °C under 1.5 MPa with 118.6 MPa shear strength (98.8% parent composite) fractured completely within the composite. Graphical abstract: Highlight: The Al-24Mg-16Ga-1Ti braze exhibited low melting range: 383 497 °C, being able to provide liquid Mg below 450 °C. The braze was able to produce fine and dispersive Ti-containing precipitated phase as in-situ reinforcement for bond seam. The braze robustly showed excellent wettability for each temperature, even at 450 °C in quasi-melting state. Sound joint produced at 500 °C under 1.5 MPa with 118.6 MPa shear strength (98.8% of composite) fractured in the composite. Mg acts as active element for wetting at low temperature, melting point increaser of Ti acts as in-situ reinforcement former.